QUALITATIVE ANALYSIS OF ORANGE PEEL ORGANIC WASTE ECOENZYME APPLICATION IN DELAYING OF RIPENING AND DECAYING FRUITS - Hafsah Hafsah; Kameliah Mushonev (El-Hayah, 2022)
Fruit damage due to overripe/rotten is a major constraint in the fruit industry. Efforts to restrain the rate of ripening are generally made by coating the fruit using certain chemicals, one of which is acid. Ecoenzyme is a liquid acidic resulting from anaerobic fermentation. Its organic acids have the potential to slow down fruit rot. This study aimed to analyse qualitatively (visually) the effect of applying specific ecoenzymes (orange peel waste) in delaying the ripening and spoilage of strawberries, bananas, green tomatoes, and red tomatoes. Tested fruits were immersed in ecoenzymes with different concentrations (100%, 50%, 25%, 12.5%, and 6.25%). Physical changes in the morphology of the fruit skin were observed every day until the fruit became ripe/rotten. Control strawberries showed a decrease in quality (mold appearance) on the 3rd day, while the concentration of 12.5% occurred on the 4th day. In bananas, a concentration of 100% can delay skin discoloration (yellowing) one day later than the control, while at a concentration of 50%, the appearance of the white mold is one day later than the control. In green tomatoes, a concentration of 50% can delay skin discoloration five days longer than controls. Concentrations of 6.25% and 50% were able to delay the emergence of white mold on red tomatoes for eight days longer than the control. Different commodities have different optimal concentrations of orange peel ecoenzymes in delaying fruit ripening/rotting. The higher acidity of the ecoenzyme is not always in line with the better result in delaying fruit ripening/rotting